PELATIHAN UNTUK MENINGKATKAN REGULASI EMOSI PADA PEKERJA SOSIAL RUMAH PERLINDUNGAN SOSIAL ANAK (RPSA) - Yuli Handayani; MM. Nilam Widyarini (Universitas Gunadarma, 2014)
The aim of this study is to measure the effectiveness emotion regulation training in children social safe house social workers, before and after the treatment. This research has 8 social workers as subject. Experiment study was use in this research with pretest post test single group involving one group with pretest (O1), treatment (X), and posttest (O2). The effect of the treatment is gained by comparing pretest (O1) and posttest (O2) score. Emotion regulation measured by Emotional Regulation Questionairre which is constructed by emotion regulation strategies and requirements. The result shows that there were significant score enhancement in two aspects, but not in one aspect respectively. The enhancement can be found in emotion regulation based on requirements and also based on expressive suppression response-focused. On the other side, there were no significant finding in emotion regulation based on reappraisal antecedent-focused strategy. Keywords: Emotion regulation, Social worker, Children social safe house